Jangha of the garbhagriha depicting a bhadra carved with the figure of deities - Temples of India Project Team (Jio Institute, 2024)
The jangha of the garbhagriha depicts a bhadra which is carved with the figure of deities. Apart from that the only decorative motif visible on the walls is a horizontal band of kirtimukha. Above the jangha, a varandika (shoulder) is carved which is made of mouldings including gaggarika and kapotapalika with a chaitya arch motif.